Container Operations Management at the Belawan Domestic Container Terminal in North Sumatra - Ridho, Syarifur; Manullang, Enny Kristina; Chandra H., Michael Ruli; Sihombing, Windra Abadi (Universitas Hang Tuah, 2025)
The Belawan Domestic Container Terminal plays a key role as the main route for domestic container flow to regions such as North Sumatra, Aceh, and Riau. However, the high volume of container movements from depots to the port occurring almost simultaneously often leads to congestion, especially in the truck stacking areas and entry gates. This study aims to analyze the container operation management at the terminal, focusing on four key management functions: planning, organizing, implementing, and controlling. The study uses a qualitative descriptive approach, collecting data through interviews, observations, and documentation. Triangulation is applied to ensure the validity of the information. The results indicate that applying these four management functions greatly contributes to smooth terminal operations. Well-structured planning and clear task organization improve operational efficiency. Coordinated execution across the vessel area, yard, and gate supports smooth processes, despite challenges such as truck queues and technical issues with the gate’s CTOS application. Time control during container receiving and delivery activities is also crucial to reducing congestion. Recommendations include implementing a more structured time allocation between receiving and delivery activities, optimizing the use of handling equipment, and increasing staff at the entry gate to speed up document checks and minimize truck queues.